1996
DOI: 10.1021/es960398s
|View full text |Cite
|
Sign up to set email alerts
|

Selective Mechanochemical Dehalogenation of Chlorobenzenes over Calcium Hydride

Abstract: We have shown that in the presence of a reactive substrate, chlorinated organic compounds can be dehalogenated by mechanical treatment, and a specific reaction product can be obtained. We have used a ball milling process at low temperature and atmospheric pressure to produce a dechlorination of up to 100% for both liquid and solid chlorinated compounds. The products of the completed reaction for trials with hexachlorobenzene and chlorobenzene were both principally restricted to benzene and chloride salts. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…In the case of chlorobenzene, the products of the completed reaction were restricted to benzene and chloride salts. Neither the breakdown of the organic species into unwanted by-products nor the formation of toxic cogeners was observed (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of chlorobenzene, the products of the completed reaction were restricted to benzene and chloride salts. Neither the breakdown of the organic species into unwanted by-products nor the formation of toxic cogeners was observed (2).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium and magnesium powders and their oxides were used as reactive substrates (1). The specific use of calcium hydride as a reducing agent allowed the dehalogenation process to be accomplished along a neater and quite straightforward path (2). In the case of chlorobenzene, the products of the completed reaction were restricted to benzene and chloride salts.…”
Section: Introductionmentioning
confidence: 99%
“…Yasumitsu et al [30] used calcium oxide as additive to destruct 1,2,3-Trichlorobenzene (TCB) by ball milling, and found that the final products contained some minor methane and ethane except carbon after 360 min milling. Loiselle et al [21] also detect methane and ethane in the end products during the process of mechanochemical treatment of chlorobenzenes. The alkane formed during milling process indicated that in the process of degradation of POPs a ring-open reaction was conducted.…”
Section: Mechanistic Interpretationmentioning
confidence: 99%
“…Loiselle et al [21] utilized CaH 2 as a source of active hydrogen and chlorinated organic compounds can be dehalogenated by mechanochemical treatment, producing a much more specific reaction in less time compared with CaO and MgO substrates. Although CaH 2 is efficient in the destruction of HCB, more consideration should be paid on its high reactivity and lability in practical implementation [22].…”
Section: Introductionmentioning
confidence: 99%
“…The former one can be regarded as the reference technique for the degradation of pollutants in liquid solutions, having a high efficiency and relatively high processing rates 8,9 . The latter one has been identified as a viable technique for the destructive treatment of pollutants dispersed in solid matrices [10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%